A unified physically based constitutive model for describing strain hardening effect and dynamic recovery behavior of a Ni-based superalloy. Issue 24 (28th December 2015) - Lin, Y.C.; Wen, Dong-Xu; Huang, Yuan-Chun; Chen, Xiao-Min; Chen, Xue-Wen
Abstract: Abstract : The strain hardening effect and dynamic recovery behavior of a Ni-based superalloy are studied by isothermal compressive tests. A new unified dislocation-density based constitutive model is developed to characterize the strain hardening effect and dynamic recovery behavior of the studied superalloy. In the developed constitutive model, some material parameters (yield stress, strain hardening coefficient, and dynamic recovery coefficient) are assumed as functions of initial grain size, deformation temperature, and strain rate. An iterative algorithm is designed to predict the high-temperature deformation behaviors under time-variant hot working conditions. The hot deformation parameters and material parameters can be updated in each strain increment. Comparisons between the experimental and calculated flow stresses indicate that the developed constitutive model can accurately describe the high-temperature deformation behavior of the studied superalloy. Furthermore, the developed constitutive model is also successfully used for analyzing time-variant hot working processes.